Effects of Different Row Spacing and Seeding Rate on Seed Yield and Some Yield Components of Birdsfoot Trefoil (Lotus corniculatus L.) in Tokat Region. - Gökalp, Sezai; Topal, Hüseyin; Yazıcı, Levent; Noyan, Ömer Faruk; Karadağ, Yaşar (My University, 2022)
Birdsfoot trefoil (Lotus corniculatus L.); is an considerable component of natural range and grassland, besides producing sufficient forage in environmentally restricted fields. In order to for increase birdsfoot trefoil cultivation, it is necessary to the sufficient quantity produce quality seeds. The information regarding the row spacing and seeding rate is important for achieving yield targets and better economic returns of birdsfoot trefoil. Our field study was carried out in order to determine the optimum row spacing and seeding rate for seed production of Sarıyıldız 60 variety that new registrated in the semi-arid climate conditions of the Central Black Sea transition zone, where this plant was not grown before. The field experiment was conducted at the using a randomized complete block split-plot design with three replicates in 2017 to 2019 growing seasons. The study were tested four different (20,40, 60 and 80 cm) row spacings and (5, 10, 15 and 20 kg-ha-1) seeding rates. Results of connectedly analysis showed that row spacing and seeding rate aplication on that the effect of on seed yield and number of pods per plant, 1000 seed weight was significant statistically but didn’t have any significant effect on number of seed per pod and harvest index. The interaction between row spacing and seedin rate did not show any significant statistical be different on seed yield and yield components. In general accepted, the number of pods per plant, the number of seeds per pod, the weight of thousand seeds and the harvest index decreases with the increase in the seed rate in all row spacings. Results showed that seed yield increases with narrower row spacing. The mean data from the three years experimental showed that the highest seed yield was obtained with plants grown in 40-20 cm row spacing’s at a seeding rate of 10-15 kg-ha-1 (24.8 and 25.7 kg per ha in respectively).